Puzzle me this? The Vietnamese reverse gender education gap - Thanos Mergoupis; Van Phan; John G. Sessions (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We investigate within the context of Viet Nam how circumstances at age 15 or 16 relate to completion of upper secondary education four years later. We exploit the longitudinal elements of the Viet Nam Access to Resources Household Survey to identify household and commune characteristics and emphasize how the effects of these characteristics vary by gender. The gender differences we find suggest that unequal treatment of girls within their households has a negative impact on their educational attainment and that in the absence of such unequal treatment the reverse gender gap would be even larger. We find nothing in terms of local labour market conditions that could explain this gap.
Keywords: J31; J32; J33; M12; 330; gender; Viet Nam; education gap